Energy efficiency tests in a full scale wind turbine gearbox. (September 2016) - Fernandes, Carlos M.C.G.; Blazquez, Luis; Sanesteban, Jorge; Martins, Ramiro C.; Seabra, Jorge H.O.
Abstract: A 850 kW wind turbine gearbox, widely used in wind farms, was used to perform efficiency tests of different wind turbine gear oil formulations. One mineral and three polyalpholephin commercially available lubricants were chosen, all them are ISO VG 320 wind turbine gear oils. Study the influence of different gear oil technologies in the overall gearbox transmission efficiency is the main objective of this work. The results show that different energetic efficiency and different oil particle counting were obtained even when the same base oil is used. Abstract : Highlights: One mineral and three polyalpholephin ISO VG 320 wind turbine gear oils were chosen. A 850 kW wind turbine gearbox was considered to perform efficiency tests. Different oil formulations, even with the same base oil, promote different energetic efficiency. Different oil formulations promote lower particle counting through oil analysis.